Evaluation of the effects of prespinal administration of Ondansetron on maternal hemodynamics - Arivumani T A; Arul Anne Rose S; Ushadevi G (International Journal of Medical Research and Review, 2016)
Introduction: Spinal anaesthesia is the preferred method of anaesthesia for elective lower segment caesarean section (LSCS). It has a shorter onset time, but is associated with hypotension and bradycardia,which at times may be deleterious to both mother and fetus.Aim of Study: To evaluate the effects of intravenous administration of ondansetron prior to spinal anaesthesia on the hemodynamic responses in the mother specifically hypotension and bradycardia.Materials and Methods: The study was a hospital based prospective, double-blinded, randomized, placebo controlled study in our teaching medical college and hospital over a period of 6 months –February to July 2015.As per inclusion and exclusion criteria of our study, study population ( 72 patients) was identified who were planned for elective LSCS. They were randomly allocated into two groups. 5 minutes prior to spinal anaesthesia, group O (n =36) received 4mg IV Ondansetron and group P (n = 36) received physiological saline. Blood pressure and heart rate were monitored once in 5 minutes for 30 minutes, and requirement of vasopressors was noted.Results: Hypotension was significantly lower in group O when compared to group P. Bradycardia was less in number in group O but it was statistically insignificant. Vasopressor requirement was also lower in group O patients.Conclusion: Intravenous Ondansetron 4mg given 5 minutes prior to spinal anaesthesia significantly reduces the hypotension. The episodes of bradycardia as well as the requirement of vasopressors in parturients were low in ondansetron group, which was found to be statistically insignificant, may be due to less number of study population.